Flow Infographic Models to Communicate Information - Widyasari; Aditya Rahman Yani (Nusantara Science and Technology Proceedings)
Some of research results related to science about the advantages of infographics have been summarized by Smiciklas (2012), including the fact that vision occupying a very large part of the brain, infographics are more easily processed by the brain than plain text, and that the brain is designed to look for something different. The majority of people are visual learners and it is estimated that 65% of the population are visual learners, so the use of infographic to communicate an information will be very appropriate. There are several types of infographic, one of which is flow infographic. Flow infographics have a function to communication an information in form of sequential flow or procedural. Through flow infographics, information can be explained step by step using attractive visualization, briefly, and still can be easily understood. The elements in visual principles can be applied to the visualization of flow infographics such as the use of numerics style, shape color transitions, shape sizes transitions, position differences, etc. Visual principles in flow infographics must be considered and understood by designers, so that the visualization of flow infographic can be more attractive and can communicate an information appropriately to readers.